1999
DOI: 10.1046/j.1460-9568.1999.00854.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aspiration versus neurotoxic lesions of the amygdala on emotional responses in monkeys

Abstract: All previous reports describing alterations in emotional reactivity after amygdala damage in monkeys were based on aspiration or radiofrequency lesions which likely disrupted ®bres of passage coursing to and from adjacent ventral and medial temporal cortical areas. To determine whether this associated indirect damage was responsible for some or all of the changes described earlier, we compared the changes induced by aspiration of the amygdala with those induced by ®bre-sparing neurotoxic lesions. Four differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
185
3
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(211 citation statements)
references
References 60 publications
22
185
3
1
Order By: Relevance
“…Consistent with these population-based findings, experimental work has shown that prepared stimuli elicit increased arousal and preferential attention relative to neutral stimuli (for review, see Ohman and Mineka (2001)). Neurobiologically, their effects are thought to be mediated by the amygdala as well as the orbitofrontal cortex (Meunier et al 1999;Kalin et al 2001;Murray and Izquierdo 2007). Our quantitative models reveal that discriminative fear conditioning occurred faster when humans were exposed to images of snakes or spiders than when they were exposed to images of abstract fractals, replicating prior work (Ho and Lipp 2014).…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Consistent with these population-based findings, experimental work has shown that prepared stimuli elicit increased arousal and preferential attention relative to neutral stimuli (for review, see Ohman and Mineka (2001)). Neurobiologically, their effects are thought to be mediated by the amygdala as well as the orbitofrontal cortex (Meunier et al 1999;Kalin et al 2001;Murray and Izquierdo 2007). Our quantitative models reveal that discriminative fear conditioning occurred faster when humans were exposed to images of snakes or spiders than when they were exposed to images of abstract fractals, replicating prior work (Ho and Lipp 2014).…”
supporting
confidence: 84%
“…Relative to fearirrelevant stimuli (e.g., flowers, mushrooms), fear-relevant stimuli have been shown to facilitate classical conditioning (Ho and Lipp 2014) and slow extinction learning (Fredrikson et al 1976; Ohman et al 1975a,b). Work in nonhuman primates suggests that innate responses to fear-relevant stimuli are mediated by the amygdala and orbitofrontal cortex (Meunier et al 1999;Kalin et al 2001;Murray and Izquierdo 2007). These structures play crucial roles in fear acquisition (Davis 1992; Maren 2001), extinction (Schiller andDelgado 2010;Milad and Quirk 2012), and value-based learning (Schoenbaum et al 1998;Holland and Gallagher 2004), and thus their preferential recruitment by prepared stimuli might enhance dynamic aversive learning.…”
mentioning
confidence: 99%
“…We believe this evidence suggests that heightened affiliative social interactions following amygdala lesions stems from a more general inability to properly perceive danger or threat in the environment and use such information to modulate social behavior adaptively. In line with this view, deficits in threat detection or fear reactivity have been specifically demonstrated for monkeys with bilateral neurotoxic amygdala lesions in both social (Machado & Bachevalier, 2006) and nonsocial settings (Izquierdo, Suda, & Murray, 2005;Kalin, Shelton, & Davidson, 2004;Kalin, Shelton, Davidson, & Kelley, 2001;Mason et al, 2006;Meunier, Bachevalier, Murray, Málková, & Mishkin, 1999). These abnormalities are not restricted to nonhuman primates, since humans with amygdala lesions also demonstrate specific deficits in identifying fearful facial expressions (Adolphs et al, 1999), rating the magnitude of fearful expressions (Adolphs, Tranel, Damasio, & Damasio, 1995) and assessing the approachability or trustworthiness of unfamiliar individuals (Adolphs, Tranel, & Damasio, 1998).…”
Section: Social Disinhibition Persists Across Contextsmentioning
confidence: 80%
“…In prairie voles, the medial nucleus of the amygdala has been shown to be involved in the regulation of aggression towards intruders (Wang et al, 1997). In primates, ablation of the amygdala bilaterally leads to increased social affiliation and decreased aggression (Emery et al, 2001;Meunier et al, 1999). These data have been taken to demonstrate a central role for the amygdala in the production of aggression, and led to the successful use of unilateral amygdalectomy in the treatment of a small number of cases of pathological aggression in human beings (Sachdev et al, 1992).…”
Section: Subregions Of the Amygdala In Emotionmentioning
confidence: 99%